Huge submandibular gland mucocele with sialolithiasis: A case report. Issue 3 (May 2017) - Yoon, Ji-Eun; Park, Jung-Hyun; Kim, Jin-Woo; Kim, Sun-Jong
Abstract: Mucocele usually originates from the minor salivary gland. It rarely develops from the submandibular gland, and on our knowledge, there had been no case report of submandibular gland mucocele with sialolithiasis occurring at the same time. This case report describes a successful treatment case of submandibular gland mucocele with sialolithiasis, evaluated by a 1-year post-operative follow-up.